TRADISI PUNGGAHAN MENJELANG RAMADHAN - Salmaa Al Zahra Ramadhani; Nor Mohammad Abdoeh (LPPM Institut Pesantren KH. Abdul Chalim, 2020)
“Punggahan” comes from the word ‘munggah’ (Javanese) which means to go up or enter a higher place. According to the world ‘munggah’ implied a change in the direction be better than the “sya’ban” month to holy month of Ramdhan and increase in faith during Ramdhan fasting. Punggahan is a tradition of sending prayers to ancestors who have died before the coming of Ramadhan, meant as a tradition of praying and giving thanks to the glorious month of Ramadhan the moon which is always awaited by its arrival in the world especially Muslims, including Muslims in Indonesia. Various preparations were made to welcome thr arrival of the month of Ramadhan including Punggahan. Punggahan aims to remind muslims that Ramadhan is coming soon, and also send prayers for people who have died. The “pungghan” tradition was introduced by Sunan Kalijaga when spreading islam in Java at the time Sunan Kalijaga used the method of cultur acculturation when spreanding Islam. Punggahan usually done in their respective homes by inviting relatives and neighbors and a kyai to lead thahlil and prayer.The menu that must be provided when uploading is apem, pasung. Pisang and ketan the four mandatory menus that must be available at the time of Pungghan. The menu that is brought during Punggahan has is own meaning by welcoming the coming of exist when Punggahan so that the meaning contained can be conveyed and can be known by readers all the word.